Transcatheter Patent Ductus Arteriosus (PDA) Device Closure: Comparative Outcomes Between Conventional Versus Single Vessel Approach - Akbar, Hajira (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine post procedural outcomes, complications, and effectiveness of transcatheter PDA closure using single-vessel and Conventional Arteriovenous access in pediatric patients.Study Design: Analytical Cross-Sectional.Place and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases (AFIC/NIHD), Rawalpindi, Pakistan; January 2024- December 2025.Methodology: The study included 269 children with isolated PDA (